Early and late change on the preclinical Alzheimer's cognitive composite in clinically normal older individuals with elevated amyloid β. Issue 9 (27th February 2017) - Mormino, Elizabeth C.; Papp, Kathryn V.; Rentz, Dorene M.; Donohue, Michael C.; Amariglio, Rebecca; Quiroz, Yakeel T.; Chhatwal, Jasmeer; Marshall, Gad A.; Donovan, Nancy; Jackson, Jonathan; Gatchel, Jennifer R.; Hanseeuw, Bernard J.; et al.
Abstract: Introduction: Sensitive detection of cognitive decline over the course of preclinical Alzheimer's disease is critical as the field moves toward secondary prevention trials. Methods: We examined amyloid β (Aβ)‐related change in several variations of the preclinical Alzheimer cognitive composite (PACC) and each individual PACC component in clinically normal (CN) older participants in the Harvard Aging Brain Study. We then examined the PACC variations in the Alzheimer's Disease Cooperative Study Prevention Instrument Study as a replication cohort. Results: Aβ+ CN individuals demonstrated longitudinal decline on all individual PACC components and all PACC variations. Aβ group differences emerged earlier when Free and Cued Selective Reminding Test Free Recall was included in the PACC. PACC decline was associated with Clinical Dementia Rating progression. Discussion: This independent data set and a replication cohort confirm the ability of the PACC to capture both early and late cognitive decline during the preclinical stages of Alzheimer's disease, which may prove advantageous in the prevention trial design.